One-Way Arbitrage and Its Implications for the Foreign Exchange Markets - Deardorff, Alan V. (Journal of Political Economy, 1979)
The relationship between spot and forward exchange rates and domestic and foreign interest rates is examined with transactions costs in all markets. Market participants choose the least-cost method of exchanging currencies in these markets, thus engaging in one-way arbitrage if that is preferable to a direct transaction. One-way arbitrage consists of using one exchange market and the two securities markets to replace a direct transaction in the other exchange market. It is shown that one-way arbitrage should prevent rates from ever departing enough from interest parity for conventional covered interest arbitrage to break even.